1999
DOI: 10.1063/1.125215
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced electrical properties of Ba0.5Sr0.5TiO3 thin films grown by ultraviolet-assisted pulsed-laser deposition

Abstract: Effect of Pt bottom electrode texture selection on the tetragonality and physical properties of Ba0.8Sr0.2TiO3 thin films produced by pulsed laser deposition J. Appl. Phys. 112, 044105 (2012); 10.1063/1.4748288 Internal residual stress studies and enhanced dielectric properties in La 0.7 Sr 0.3 CoO 3 buffered ( Ba , Sr ) TiO 3 thin films

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…Similar reduction in leakage characteristics have been observed for Ta 2 O 5 films UV-annealed (172 nm eximer lamp) at 400 C/ 60 min, 37 Ta 2 O 5 films grown by photo-pulsed laser vapor deposition PLD, 38 for UVA HfO 2 films (mercury lamp), 46 and for BST films grown by UV-PLD. 47 Our results demonstrated that the reduction in leakage current density (Fig. 5) paralleled the reduction in dielectric loss (Fig.…”
Section: Resultssupporting
confidence: 59%
“…Similar reduction in leakage characteristics have been observed for Ta 2 O 5 films UV-annealed (172 nm eximer lamp) at 400 C/ 60 min, 37 Ta 2 O 5 films grown by photo-pulsed laser vapor deposition PLD, 38 for UVA HfO 2 films (mercury lamp), 46 and for BST films grown by UV-PLD. 47 Our results demonstrated that the reduction in leakage current density (Fig. 5) paralleled the reduction in dielectric loss (Fig.…”
Section: Resultssupporting
confidence: 59%
“…Material systems that have been, and continue to be, explored for use as alternative gate dielectrics include Ta 2 O 5 , 2 TiO 2 , 3 ZrO 2 , 4 Al 2 O 3 , 5 HfO 2 , 6 La 2 O 3 , 7 Y 2 O 3 , 7 and (Ca,Ba,Sr͒TiO 3 . [8][9][10] For MOSFET structures, the oxide/semiconductor interface largely determines the properties of the device. Interfacial layers resulting from reaction of the deposited oxide with silicon can severely limit the effective capacitance/area realized.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, BST thin films attracted much attention and turned into one of the predominant materials for UFPAs for its outstanding pyroelectric properties. The BST thin films usually have been deposited by radio frequency (RF) sputtering [10], metal organic chemical vapor deposition (MOCVD) [11], pulsed laser deposition (PLD) [12] and sol-gel methods [13]. Compared with the conventional methods, sol-gel technique offers a homogeneous distribution of elements on a molecular level, ease of composition control, thigh purity, the possibility of low temperature processing, and the ability to coat large and complex area substrates [14].…”
Section: Introductionmentioning
confidence: 99%